The microfinance revolution, vol. 2 : lessons from Indonesia - Robinson, Marguerite (Washington : World Bank Publications, 2002)
The revolution occurring in finance for low-income people refers to commercial microfinance--the delivery of financial services to the economically active poor on a large scale through competing, financially self-sufficient institutions. 'Lessons from Indonesia', volume 2 of 'The Microfinance Revolution', examines in the Indonesian context the principles and practices of commercial microfinance that were explored and analyzed in volume 1. The first country to develop profitable microfinance on a large scale, Indonesia is home to the world's oldest and largest commercial microfinance institutions, as well as many others.The book examines many financial institutions, with a special emphasis on Bank Rakyat Indonesia's microbanking system, which in the mid-1980s was transformed from a failed subsidized credit program to a nationwide commercial financial intermediary that now profitably provides microfinance services--savings and credit--to more than 20 million people. Commercial microbanking remained stable and profitable in Indonesia even as the country's financial system collapsed during the recent crisis. This volume shows why, and offers crucial lessons for developing countries everywhere.
Scholarly & Professional
Keywords: Finance